Saving the world? how CSR practitioners live their calling by constructing different types of purpose in three occupational stages - Fontana, Enrico; Frandsen, Sanne; Morsing, Mette (Springer, 2023)
Much attention in the meaningful work literature has been devoted to calling as an orientation toward work characterized by a strong sense of purpose and a prosocial motivation beyond self-gain. Nonetheless, debate remains as to whether individuals change or maintain their calling, and especially whether they live their calling differently in different occupational stages. In this article, we respond to this conundrum through an analysis of the corporate social responsibility (CSR) occupation—substantiated by interviews with 57 CSR practitioners from Swedish international companies who are living their calling. We demonstrate that social/commercial tensions affect these CSR practitioners, fueled by a divide between their social aspirations and the commercial goals, and prompt them to respond in a way that impacts how they construct the purpose of their work. Subsequently, we induce three stages of the CSR occupation—early-, mid- and late-stage—and conceptualize three types of purpose in each stage—activistic, win–win and corporate purpose. By uncovering how and why CSR practitioners respond to social/commercial tensions and construct different types of purpose in each stage of the CSR occupation, we show that individuals can live the same calling in multiple ways. Hence, our article advances the meaningful work literature as well as studies of micro-CSR.
Keywords: Meaningful work; Calling; Purpose; Occupational stages; Social/commercial tensions; CSR practitioners; International companies